Jungian dream interpretation as a counseling tool for clients with emotional difficulties - Lopez, Eduardo V. (Animo Repository, 1989)
This study attempts to determine the therapeutic effectiveness of Jungian dream interpretation in the resolution of one's emotional difficulties. The study used an idiographic (n=1) design and the subjects consisted of two (2) low-income, Filipino/English speaking college educated Filipinos whose ages ranged between 27 and 29 years old. The therapeutic interventions were administered using the standardized procedures of Jungian dream interpretation. After meeting each counselee for four weeks once a week, the therapeutic intervention was withdrawn for another four weeks of one meeting each. This time counseling went on and the counselor used different techniques other than dream interpretation as may be necessary. After four times of meeting each counselee, therapeutic intervention was reinstated for another four weeks of once a week session for each counselee. The number of sessions was 12 for each counselee, excluding the pretest and feedback-gathering-follow-up sessions. The results showed that the counselees exhibited varying degrees of development in both the process and outcome variables in a direction which was perceived as positive by the counselees themselves, and some of their significant others. The researcher made some comments and recommendations. These changes were assessed after a period of about 10 months from the time therapy was instituted. Unlike Counselee 1, Counselee 2 showed positive changes in both the process and outcome variables.In so far as there were only two cases used in this study and therefore cannot be considered as typical sample of the population they represent, the following tentative conclusions were drawn: 1) The Jungian dream interpretation evoked in the counselees in both the process and outcome variables their deepest personal concerns/preoccupations. 2) The dream reports, discussions and analyses led the counselees to come up with possibilities for growth relative to their personal concerns/preoccupations. 3) Dream analysis elicited more counselee verbalizations than when counseling was done without the help of dreams as its raw materials. 4) Therapeutic effectiveness of Jungian dream interpretation was not lost even if it was withdrawn which might explain therapy's permanency of effect upon the counselee. 5) Through dream reports, discussions and analyses, counselees were led to develop insight into their personal wealth of wisdom thus making the counseling sessions workshops for self-discovery and problem solving as well. 6) No amount of psychological intervention within the framework of Jungian interpretation will work if the individual seeking help does not give up or is not willing to give up his defenses. 7) Listening to others' ideas and observing their behaviors are likely to assist the person to modify his own self-defeating behaviors. 8) Though one may still be uncertain and confused at the termination of therapy, he will probably get a lot of learning through interaction with others.